Simulation of a turning ski using ice cutting data - Tada, N.; Hirano, Y. (Sports Engineering, 1999)
Centripetal forces acting on a ski-skier system allow turning motions while alpine skiing, i.e. when the skier places the skis` longitudinal axes at an angle inclined away from the velocity vector and simultaneously edges the skis into the snow, oblique cutting forces are generated in icy, hard snow. In this paper, we determine such ice cutting forces experimentally, and after deriving empirical equations for representing them, numerically simulate the tracks of turning alpine skis.